Wing transparency in butterflies and moths: structural diversity, optical properties, and ecological relevance. Issue 4 (17th August 2021) - Gomez, Doris; Pinna, Charline; Pairraire, Jonathan; Arias, Mónica; Barbut, Jérôme; Pomerantz, Aaron; Daney de Marcillac, Willy; Berthier, Serge; Patel, Nipam; Andraud, Christine; Elias, Marianne
Abstract: In water, transparency seems an ideal concealment strategy, as testified by the variety of transparent aquatic organisms. By contrast, transparency is nearly absent on land, with the exception of insect wings, and knowledge is scarce about its functions and evolution, with fragmentary studies and no comparative perspective. Lepidoptera (butterflies and moths) represent an outstanding group to investigate transparency on land, as species typically harbor opaque wings covered with colored scales, a key multifunctional innovation. Yet, many Lepidoptera species have evolved partially or fully transparent wings. At the interface between physics and biology, the present study investigates wing transparency in 123 Lepidoptera species (from 31 families) for its structural basis, optical properties, and biological relevance in relation to visual detection (concealment), thermoregulation, and protection against UV. Our results suggest that transparency has likely evolved multiple times independently. Efficiency at transmitting light is largely determined by clearwing microstructure (scale shape, insertion, coloration, dimensions, and density) and macrostructure (clearwing area, species size, or wing area). Microstructural traits, scale density and dimensions, are tightly linked in their evolution, with different constraints according to scale shape, insertion, and coloration. Transparency appears highly relevant for concealment, with size‐dependent variations. Links between transparency and latitude are consistent with an ecological relevance of transparency in thermoregulation, and not so for protection against UV radiation. Altogether, our results shed new light on the physical and ecological processes driving the evolution of transparency on land and underline that transparency is a more complex coloration strategy than previously thought.